Pelatihan Kompetensi Pemandu Wisata Serikat Pekerja Pariwisata Borobudur di Desa Wisata Candirejo dalam Persiapan Sertifikasi - Izza Ulumuddin Ahmad Asshofi; Joseph Aldo Irawan; Emik Rahayu (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Tourism, which is starting to revive at this time, is a momentum that is welcomed by tourism actors in the Borobudur Super Priority Tourism Destination area. Seeing opportunities for revival, the Candirejo tourism village community who are members of the SPPB (Borobudur Tourism Workers' Union) need trainings in preparation for competency certification as legal evidence of related competence. The intended preparation is endeavored to fulfill the elements of attitude, skills and knowledge of a tour guide contained in the competency unit of the tour guide scheme. This paper aims to measure the competence of SPPB Tour Guides in preparation for competency certification. The training method is carried out through lectures, discussions, pre-tests and post-tests. The results of the training show an increase in competence as measured by the results of the post-test compared to the results of the pre-test.